Price setting in the euro area: some stylised facts from individual producer price data - Philip Vermeulen; Daniel Dias; Maarten Dossche; Erwan Gautier; Ignacio Hernando; Roberto Sabbatini; Harald Stahl (European Central Bank (ECB), 2007)
This paper documents producer price setting in 6 countries of the euro area: Germany, France, Italy, Spain, Belgium and Portugal. It collects evidence from available studies on each of those countries and also provides new evidence. These studies use monthly producer price data. The following five stylised facts emerge consistently across countries. First, producer prices change infrequently: each month around 21% of prices change. Second, there is substantial cross-sector heterogeneity in the frequency of price changes: prices change very often in the energy sector, less often in food and intermediate goods and least often in non-durable nonfood and durable goods. Third, countries have a similar ranking of industries in terms of frequency of price changes. Fourth, there is no evidence of downward nominal rigidity: price changes are for about 45% decreases and 55% increases. Fifth, price changes are sizeable compared to the inflation rate. The paper also examines the factors driving producer price changes. It finds that costs structure, competition, seasonality, inflation and attractive pricing all play a role in driving producer price changes. In addition producer prices tend to be more flexible than consumer prices.
Keywords: E31; D40; C25; 330; price-setting; producer prices; Preismanagement; Volatilität; Deutschland; Frankreich; Italien; Spanien; Belgien; Portugal